A Meta-Transcriptomics Survey Reveals Changes in the Microbiota of the Chinese Mitten Crab Eriocheir sinensis Infected with Hepatopancreatic Necrosis Disease - Shen, Huaishun; Zang, Yanan; Song, Kun; Ma, Yuanchao; Dai, Tianhao; Serwadda, Ali (Frontiers in Microbiology, 2017)
Infection of the freshwater Chinese mitten crab Eriocheir sinensis with hepatopancreatic necrosis disease (HPND) has been a major problem in the crab-cultivated Chinese Province of Jiangsu since 2015. To explore the aetiology of HPND, meta-transcriptomic libraries of the hepatopancreata from crabs with and without HPND were constructed. Comparison analyses showed that there were no statistically significant differences in viral and microsporidial communities in the hepatopancreata of diseased and healthy crabs. Bacteroidetes, Proteobacteria, and Firmicutes were the most dominant bacterial phyla in the hepatopancreata of healthy crabs, with a combined prevalence of 93%. However, a decrease in bacterial diversity and a striking shift in the microbial composition were found in the hepatopancreata of crabs infected with HPND. Tenericutes was the most prevalent bacterial phylum in diseased crabs (31.82%), whereas its prevalence was low in healthy crabs (0.02%). By contrast, the prevalence of Bacteroidetes was significantly lower in crabs with HPND (3.49%) than in crabs without HPND (41.04%). We also found that the prevalence of Actinobacteria was higher in crabs with HPND (16.70%) than in crabs without the disease (4.03%). The major bacterial family within the Tenericutes phylum in crabs with HPND was detected by polymerase chain reaction and determined to be Mycoplasmataceae. In conclusion, there were striking changes in the microbiota of diseased and healthy crabs. Specifically, the prevalence of bacteria belonging to Tenericutes and Actinobacteria phyla increased, whereas the prevalence of bacteria belonging to the Bacteroidetes phylum decreased in crabs with HPND, clearly pointing to an association with HPND.